Reckoning with truth globally: Decolonial possibilities - Vanessa Barolsky; L Rodriguez Castro; Yin Paradies (2024)
This Special Issue interrogates the limitations and possibilities of truth within global efforts to address historical injustice. Over the past 30 years truth commissions have become ubiquitous in response to authoritarian regimes and colonial legacies. However, their ability to facilitate meaningful transformation is increasingly contested. In this editorial we explore what a decolonial reckoning, rather than reconciliation, with the past and colonial logics of power, might mean. In doing so, we argue that the liberal, modernist imaginary of justice on which many truth processes have been premised, is constraining our imagination of more radical ‘fugitive’ forms justice. Drawing from contributions from Australia and other global contexts this special issue investigates these limitations and the transformative potential of truth as a decolonial, sovereign, embodied and relational praxis. Contributors engage with the pluriversality of truth in ways that trouble the nation-state and centre the sovereignty and onto-epistemology of racialised and First Nations peoples, often excluded from transitional justice processes, thus offering pathways for radical resistance, resurgence and prefigurative transformation.